1988
DOI: 10.1037/0021-843x.97.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia is associated with altered orienting activity: Depression with electrodermal (cholinergic?) deficit and normal orienting response.

Abstract: The import of a recent consensus that a distinctive subgroup of schizophrenics is marked by nonreactivity of the orienting response (OR) to innocuous stimuli has been made ambiguous by reports of similar nonreactivity among depressives. To test this, we studied 50 schizophrenics (14 drug free), 50 depressives (20 drug free), and 50 normal controls. Stimuli were 1000 Hz (60 dB) or 2000 Hz (58 dB) 1-s tones delivered either to the left or right ear. A subsample of each group was told they need do nothing during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…Thus, the lower SCL, OR and SCOR conductance amplitudes are, the larger the scores in BDI, STAI-E and STAI-R. Some authors have observed similar results [34,42], but other studies have not detected any correlation [26,38,43,44]. In the present research, the depressive sample displayed high scores in STAI which would be able to reflect elevated anxiety.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the lower SCL, OR and SCOR conductance amplitudes are, the larger the scores in BDI, STAI-E and STAI-R. Some authors have observed similar results [34,42], but other studies have not detected any correlation [26,38,43,44]. In the present research, the depressive sample displayed high scores in STAI which would be able to reflect elevated anxiety.…”
Section: Discussionsupporting
confidence: 70%
“…It is possible that electrodermal hyporeactivity reflects the operation of underlying mechanisms that are shared with other disorders besides those in the externalizing spectrum. Reduced orienting reactivity and accelerated rates of habituation have previously been linked to diverse disorders ranging from schizophrenia to mood disorders (Bernstein et al, 1988; Iacono, Ficken, & Beiser, 1999). Indeed, reduced SCR frequency may be an indicator of general psychopathology severity rather than a psychophysiological marker associated with a specific type of mental illness (Wahlund, Sorman, Gavazzeni, Fischer, & Kristiansson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…3.4.2.2). An interesting hypothesis on the difference between nonresponding in depressives and schizophrenics has been developed by Bernstein et al (1988) who found similar patterns in SCR nonresponding but differences in finger pulse volume between both groups. Since depressives showed intact ORs in the finger pulse amplitude measure, their deficit in electrodermal responsivity may be due to their possible deficit in peripheral cholinergic mediation, thus having a different origin as in schizophrenics.…”
Section: Eda In Depressive Patientsmentioning
confidence: 99%